Pharmaceutical cognitive enhancement among Slovenian university students - Pustovrh, Toni (Teorija in praksa, 2014)
Over the past two decades, the concept of human enhancement - the idea that the normal capabilities of healthy people can be enhanced through direct technological interventions into the body - has garnered increasing attention in some scientific circles. Most potential enhancement technologies are still in research and development, with a few exceptions, such as pharmaceutical drugs that can increase concentration, memory and wakefulness. Such use has been conceptualized as "pharmaceutical cognitive enhancement" (PCE), and PCE use among students is cited as signifying an important new trend that requires expert and public attention. The article takes up the call to explore PCE trends in national contexts. The results of an online survey covering experiences and attitudes towards PCE among 445 undergraduate students at the University of Ljubljana, Slovenia, have shown that 6,1 % have already used PCE. Regarding attitudes, 26 % of users and 20 % of nonusers though that healthy adults should be permitted to use PCE according to their own judgment, while 33 % of users and 21 % of nonusers stated they will probably use PCE in the future. A tangible percentage of PCE use is present, but it requires interpretation and several different contextual interpretations are proposed. Ultimately, societies will need to decide how to interpret and potentially address the trend at the national and possibly international level.
Keywords: Cognitive neuroscience; Kognitivna nevroznanost; Slovenia; Slovenija; student; Students; Substance abuse; Študenti; Zloraba snovi